2022
DOI: 10.1002/jnr.25010
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin reuptake transporter modulates mitochondrial copy number and mitochondrial respiratory complex gene expression in the frontal cortex and cerebellum in a sexually dimorphic manner

Abstract: Neuropsychiatric and neurodevelopmental disorders such as major depressive disorder (MDD) and autism spectrum disorder (ASD) are complex conditions attributed to both genetic and environmental factors. There is a growing body of evidence showing that serotonergic signaling and mitochondrial dysfunction contribute to the pathophysiology of these disorders and are linked as signaling through specific serotonin(5-HT) receptors drives mitochondrial biogenesis. The serotonin transporter (SERT) is important in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…However, it is important to note that all these previous studies were performed in male rats only. A recent review highlights the heavy sex bias in SERT research which has worsened since the turn of the millennium (Thorne et al 2022b ). Therefore, this study provides further justification to include females in order to get a full picture of the role of the SERT in drug addiction, particularly given the variability in human studies described in the introduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that all these previous studies were performed in male rats only. A recent review highlights the heavy sex bias in SERT research which has worsened since the turn of the millennium (Thorne et al 2022b ). Therefore, this study provides further justification to include females in order to get a full picture of the role of the SERT in drug addiction, particularly given the variability in human studies described in the introduction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the influence of the SERT on mitochondria has been reported [55]. A previous study showed a negative correlation between SERT expression and mitochondrial copy number in the brains of male rats, while reduced SERT expression led to a decrease in mitochondrial copy number in females [55]. Regardless of the unclear mechanisms underlying the impact of SERT on mitochondria and the sex-related dimorphic regulation, these findings implicate the involvement of serotonin signaling in mitochondrial biology.…”
Section: Serotonin and Mitochondrial Regulation In Neurobiologymentioning
confidence: 72%
“…This suggests that the role of serotonin in regulating mitochondria is not exclusive to neural cells. Additionally, the influence of the SERT on mitochondria has been reported [55]. A previous study showed a negative correlation between SERT expression and mitochondrial copy number in the brains of male rats, while reduced SERT expression led to a decrease in mitochondrial copy number in females [55].…”
Section: Serotonin and Mitochondrial Regulation In Neurobiologymentioning
confidence: 99%
“…Patients with ASD often exhibit hyper-serotonemia, and 5-HT levels are significantly predictive of ASD development ( 65 ). Its receptor serotonin transporter protein (SERT) was found to regulate synaptic serotonin, modulating mitochondrial copy number and mitochondrial respiratory complex gene expression in the frontal cortex and cerebellum in a sexually dimorphic manner, which could help explain the gender bias in ASD prevalence ( 66 ). Catecholamines are neurotrophic and regulatory factors, with DA primarily responsible for attention, reward motivation, motor and communication skills ( 67 ).…”
Section: Neural Pathwaysmentioning
confidence: 99%